M is for magic - Gaiman, Neil.; Kristiansen, Teddy H. (New York : HarperCollins, 2007)
Eleven stories that involve strange and fantastical events.
Instructions -- The case of the four and twenty blackbirds -- Troll bridge -- Don't ask Jack -- How to sell the Ponti Bridge -- October in the chair -- Chivalry -- The price -- How to talk to girls at parties -- Sunbird -- The witch's headstone.
Keywords: Children's stories, American; Short stories